Crystalline LaCoO3 perovskite as a novel catalyst for glycerol transesterification - Phadtare, Deepshree; Kondawar, Sharda; Athawale, Anjali; Rode, Chandrashekhar (Molecular Catalysis, 2019)
LaCoO3 perovskite was synthesized using sol-gel method by nitrate and acetate precursors of La and Co with varying molar ratios of La and Co (1:1, 1:2 and 2:1). This was found to be an unique strategy to obtain highly crystalline LaCoO3 perovskite material without using any chelating agent. The variation of precursors was found to influence their crystallinity however, variation in molar ratio in the range of 0.5-2, did not affect the formation of perovskite framework. The formation of pure perovskite phase (around or > 80%) could be achieved by combination of acetate and nitrate precursors while, the combination of acetate- acetate or nitrate- nitrate precursors resulted in low phase purity for the perovskite due to the formation of secondary phases like La2O3 and Co3O4. Very interestingly, such combination of perovskite and pure oxide phases contributed to enhancement of basic sites which catalyzed the glycerol transestrifiaction with DMC (dimethyl carbonate) to GC (glycerol carbonate) and GD (glycidol). Among all the catalysts studied, NAP-2 showed highest efficiency in terms of 98% glycerol conversion and 77% GC and 22% GD selectivities. The highlight of this work is that first step glycerol transesterification with DMC required basic sites of either metal oxide or perovskite but for cascade reaction involving decarboxylation required both metal oxide as well as LaCoO3 perovskite phase.